Awareness of Dietary Choice and Food Intake by Married Male Workers Living in a Metropolitan Area - Yamashita, Naoko; Nishikido, Hiromi; Ishida, Hiromi; Morino, Mayumi (Eiyōgaku zasshi, 2006)
This study examines the awareness of dietary choice and food intake by a questionnaire survey. The 300 subjects were married male workers (aged 30-59) living in a metropolitan area. Their key concerns about eating differed among breakfast, lunch and dinner. With regard to breakfast, the key concern was “eating quickly, ” while for lunch, interest was focused on “eating cheaply, ” and for dinner, attention was paid to “good nutritional balance.” The subjects of the study were aware that they should “eat as much vegetable food as possible” and “consider nutritional balance, ” but 30.4% of their total energy intake came from fat. Furthermore, regarding the intake of particular food items, more than 80% of the respondents did not eat the recommended amounts of fruits, tubers, dairy products, mushrooms and seaweed, and green and yellow vegetables. More than 30% of the subjects ate no dairy products, beans and bean products, tubers, or fruit. The level of this awareness changed with age, and the energy intake of those who spent a long time eating dinner and drinking alcohol was significantly higher than that of the other subjects.